SUPPORTING AND INHIBITING FACTORS IN THE FORMATION OF MORALS THROUGH HABITUATION METHODS FOR MAS AMALIAH STUDENTS SUNGGAL - Hadi Saputra Panggabean; Nurhalima Tambunan; Rita Novianti (Proceeding International Seminar of Islamic Studies, 2023)
A good and appropriate PAI teacher strategy can certainly provide changes to student morals. On the contrary, the strategy of bad and inappropriate PAI teachers can be the cause of the failure of Islamic education in fostering student morals in schools so far, because many students are lacking or still low in morals. This is due to the failure to instill and cultivate morals. The formation of morals through various educational institutions and through various methods continues to be developed, as will later be developed through habituation methods. This shows that morals do need to be fostered, and this guidance has resulted in the formation of Muslim individuals who have a noble character, obey Allah and His Messenger, respect for parents, love for fellow creatures of Allah. But on the contrary, if the morals of the child are not fostered, problems will arise such as naughty children who always disturb society etc. Using the habituation method has a very big influence on the personal formation of MAS Amaliah Sunggal students, because habituation in education is the most influential method for children. The child first sees, hears and socializes with his parents. In this case the educator becomes the best example in the view of the child. What is the behavior of the parents will be imitated by him. We as educators should exemplify good deeds to our students, if we exemplify the ugly then our students will model the ugly but if we exemplify the good then our students will follow the example of the good